Issues of Implementing The “Digital Court” Concept in Judicial Activity - Javohir Bahodir ogli Khaydarkulov (Scientific Trends, 2026)
This article analyses the implementation of the “Digital Court” concept in the activities of courts, highlighting its significance for improving the efficiency, transparency, and accessibility of judicial proceedings. Particular attention is paid to the use of digital technologies in court administration and case management. In addition, the article examines relevant foreign experience in this area and identifies key aspects that may be adapted to the national judicial system.
Keywords: Digital Court; Digital Legal Assistant; Electronic Case Management System; Electronic Notification.